Community-acquired pneumonia requiring hospitalization: rational decision making and interpretation of guidelines. Issue 3 (May 2017) - Postma, Douwe F.; van Werkhoven, Cornelis H.; Oosterheert, Jan Jelrik
Abstract : Purpose of review: This review focuses on the evidence base for guideline recommendations on the diagnosis, the optimal choice, timing and duration of empirical antibiotic therapy, and the use of microbiological tests for patients hospitalized with community-acquired pneumonia (CAP): issues for which guidelines are frequently used as a quick reference. Furthermore, we will discuss possibilities for future research in these topics. Recent findings: Many national and international guideline recommendations, even on critical elements of CAP management, are based on low-to-moderate quality evidence. Summary: The diagnosis and management of CAP has hardly changed for decades. The recommendation to cover atypical pathogens in all hospitalized CAP patients is based on observational studies only and is challenged by two recent trials. The following years, improved diagnostic testing, radiologically by low-dose Computed Tomography or ultrasound and/or microbiologically by point-of-care multiplex PCR, has the potential to largely influence the choice and start of antibiotic therapy in hospitalized CAP patients. Rapid microbiological testing will hopefully improve antibiotic de-escalation or early pathogen-directed therapy, both potent ways of reducing broad-spectrum antibiotic use. Current guideline recommendations on the timing and duration of antibiotic therapy are based on limited evidence, but will be hard to improve.